Model Matematika Kerusakan Sumber Daya Hutan di Indonesia - Nur Suci; Arnellis Arnellis; Media Rosha (Journal of Mathematics UNP, 2014)
Abstract – The Degradation of forestry resources is a serious problem is faced by Indonesian country.  The growth of  population people  and augment industrialization in Indonesia gave a negative effect to forestry resources. Its happen if the utilization continuously without preservation. The purpose of this study is to see the dynamic degradation of forestry resources that can be done by modeling the influence population growth and augment industrialization to forestry resources in the form of a mathematical model.  The form of mathematical models equations a non-linear differential equations system. Furthermore Mathematical model that we get be analysised and the result is interprestationed to answer the problem. According the analysis of mathematical model dynamics degradation of forestry resources in Indonesia is gotten by two types of fixed point; fixed point  interference free ( ) and fixed point interference ( and ), and then we get obtained the stability of each fixed.   Keywords – Degradation of Forestry, Industrialization, Mathematical  Models, Population People Stability.